Müller glial cells alterations in a retinal degeneration mouse model - Vallese, Harmonie Agostina (2022)
Müller glial cells (MGCs) are stem cells and promote photoreceptors (PHRs) survival in the retina. However, multiple injuries to the retina trigger “reactive gliosis,” which might lead to neuronal death. We previously demonstrated that MGC in rd1 mouse (a retina degeneration model) have early alterations in morphology and in reactive and stem cell markers; and stem cell markers are partially restored when rd1 MGC are co-cultured with wt neurons. This suggests that impaired neuro-glial crosstalk affects the stem cell potential of rd1 MGC. We now investigated whether alterations in the expression of extracellular matrix (ECM) proteins participate in rd1 impaired crosstalk. Using mixed neuro-glial (NG) cultures obtained from postnatal 2 days rd1 and wt mice retinas, we analyzed by immunocytochemistry, osteonectin and fibronectin (FN) expression and focal adhesions (FA) at 6 days in vitro. Also, rd1 mixed NG cultures were seeded on culture dishes previously treated with ECM-enriched conditioned medium (ECM-CM), to analyze rd1 MGC morphology, FAs, proliferation, and PHR survival (using BrdU and DAPI, respectively). In addition, rd1 mixed NG cultures were supplemented with conditioned medium obtained from wt mixed NG cultures (NG-CM), and conversely, wt NG cultures were supplemented with conditioned medium from rd1 cultures to analyze MGC morphology. Our results showed a decrease in osteonectin expression, a fibrillary FN expression, and a decreased number and length of FAs. Also, FAs cortical locations were different in rd1 and in wt MGC mixed NG cultures. Noteworthy, ECM-CM pretreatment restored rd1 MGC cytoplasmic extension and their FAs and promoted rd1 MGC proliferation, and decreased PHR death. Likewise, preliminary results showed that wt NG-CM supplementation in rd1 mixed cultures expanded MGC lamellipodia and increased PHR survival. These results suggest that rd1 MGC present alterations in EMC protein synthesis and/or secretion, and that wt ECM supplementation improves MGC morphology and functionality.